ANGLICISMS IN THE FRENCH LANGUAGE: LINGUISTIC AND SOCIAL ASPECTS - Maryna Kostiuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The primary objective of this article is to observe the phenomenon of "anglicism" in the French language and to study the causes and the reasons for the frequent use of English borrowings. English, as an international language, influences French strongly despite the efforts of French purists to protect their language from it. This article describes and analyses the influence of the English language on the French language. It addresses the notion of franglais as a social phenomenon in French that can be observed at different levels of life. Borrowings from English, or anglicisms, represent one of the most important types of semantic neologisms in the French language. There are six types of anglicisms in French: semantic, lexical, syntactic, morphological, phonetic and graphical. The repeated use of borrowings in French results in the modification of their semantic structure according to the peculiarities and needs of the French language. Anglicisms in French acquire different shades of meaning. The most frequent English borrowings have the suffix -ing like shopping or camping. The English suffixes -are and -al have been transformed into the French suffixes -aire, -eur, -el, which are more typical for the French language. Many popular English words are used in the business sphere, not only in France but all over the world (brainstorming; mainstream; process; workshop; bullet points; burnout; conference call; desk; one-to-one). Language policy in France, with its main representative the Académie française, tries to control the redundant use of English words in this era of globalisation.